ANALISIS KEMAMPUAN PEMECAHAN MASALAH TAHAPAN POLYA DALAM MENYELESAIKAN PERSAMAAN DAN PERTIDAKSAMAAN LINEAR SATU VARIABEL - Ellycia Nur Christina; Alpha Galih Adirakasiwi (IKIP Siliwangi, 2021)
This study aims to describe the mathematical problem solving ability of Polya stages in solving equation material and linear inequality of one variable. The research method used is descriptive qualitative research. The population in this study was grade VII students of SMP Kota Bekasi with a subject of 40 students. Data collection techniques are five test instruments for mathematical problem solving capabilities. Based on the results of the study obtained mathematical problem solving skills of students are different there are in the high, medium and low categories. Of the 40 students who were subjected to the study, 26 students with low mathematical problem solving skills with a percentage of 65%. Therefore, the mathematical problem solving ability of SMP grade VII in solving equation material and linear inequality of one variable is relatively low.